Influence of σ phases on the microstructure and properties of S32760 super duplex stainless steel - LI Guo-ping; PEI Hai-xiang; LI Jian-chun; ZHANG Shou-lu (工程科学学报, 2016)
The precipitation behavior of σ phases in W-containing S32760 super duplex stainless steel was studied by aging treatment experiments. The morphology and chemical composition of the σ phases were investigated by scanning electron microscopy and transmission electron microscopy. The effects of the σ phases on the mechanical properties and corrosion resistance of the stainless steel were analyzed additionally. The σ phases composed of Fe-Cr-Mo-W have a tetragonal structure and abundantly precipitate at 850-1000℃ in the stainless steel with quite high strength and hardness and extremely poor plasticity,for example,the elongation is lower than 4.0%. There are still a few of σ phases at 1050℃,though the elongation increases to 31.1%,the values of impact toughness are discrete,and the average impact energy is low. Until 1080℃,the σ phases completely dissolve to the matrix. The tensile strength and the elongation are 640 MPa and 35.5%,and the longitudinal and the transverse impact energies averagely reached to 217 J and 110 J,respectively. As the treatment temperature increasing,the pitting potential(Eb) improves,and the mass loss rate of pitting corrosion decreases. The pitting potential of the stainless steel treated at 1080℃ is up to 1246 m V,while the mass loss rate decreases only to 0.005-0.007 g·m-2·h-1 when being soaked in a 3.5% Na Cl solution at 50℃.